Taxonomic notes on two endemic geometrine genera from Middle Asia (Lepidoptera: Geometridae, Geometrinae) - Viidalepp, Jaan; Kostjuk, Igor (Zootaxa, 2021)
The genus Hissarica Viidalepp (Geometridae, Geometrinae) is restored from synonymy with Xenochlorodes Warren. The moths and their male and female genitalia are illustrated and characterized in comparison with those of Hierochthonia Prout and Xenochlorodes. Taxonomic positions of “Hierochthonia” alexandraria Prout and Eucrostes petitaria Christoph are discussed and the new genus Ratsa Viidalepp & Kostjuk gen. nov. is established for them, creating the new combinations Ratsa alexandraria Prout and Ratsa petitaria Christoph.